Cross-cultural mentoring - Helen DeWaard; Rekha Chavhan (Journal of Teaching and Learning, 2020)
This paper offers insight from an informal cross-cultural mentoring experience of course development in higher education framed by the UNESCO Chair on Open Technologies for Open Educational Resources and Open Learning project. The Open Education for a Better World is a tuition-free international online mentoring program established to unlock the potential of open education in achieving the United Nation Sustainable Development Goals. Drawing from mentor/protégé conversations and reflections, and examining the experiences of mentoring in the development of an online course for Indian teacher education faculty development, the authors illuminate a pathway toward building professional relationships and professional learning beyond borders and boundaries. This paper describes how mentorship can develop digital competencies foundational for transferring tacit knowledge about planning, designing, recording, implementing, and evaluating teaching and learning in education. Explicit knowledge-building for professional learning within a supportive mentoring relationship is explored.